Clinical causes and treatment of the thrombotic storm. Issue 6 (December 2012) - Ortel, Thomas L; Kitchens, Craig S; Erkan, Doruk; Brandão, Leonardo R; Hahn, Susan; James, Andra H; Kulkarni, Roshni; Manco-Johnson, Marilyn J; Pericak-Vance, Margaret; Vance, Jeffery
Thrombotic storm represents an extreme prothrombotic phenotype, characterized by multiple thrombotic events affecting diverse vascular beds occurring over a brief period of time. Thrombotic events involve venous and arterial circulation, including unusual locations, such as cerebral sinus venous thrombosis, intra-abdominal thromboembolic occlusions and microvascular events. Some patients will have antiphospholipid antibodies, but a significant number have no identifiable hypercoagulable state. The mainstay of treatment consists of anticoagulant therapy, although some patients appear to benefit from the addition of immunomodulatory therapies. Other disorders that share this thrombotic storm phenotype include catastrophic antiphospholipid syndrome, spontaneous heparin-induced thrombocytopenia and similar aggressive clinical disorders. Ongoing studies are focused on identifying underlying genetic factors that may predispose patients to develop this extreme clinical phenotype.